Vous êtes sur la page 1sur 34

, ,

,

, , ,

= α + β

= α + β + ε

ε

α β

= α + β = α + β + ε ε α β

= α + β + ε

α β

α β

= α + β + ε α β α β

α β

α β → α ˆ ˆ β

αˆ

ˆ

β

α β → α ˆ ˆ β

ˆ

εˆ ˆ

ˆ ε ˆ ˆ −

εˆ + εˆ + εˆ + εˆ + εˆ + ··· + εˆ

= εˆ

εˆ

ˆ

= (

ˆ )

= εˆ

α β

ε ˆ + ε ˆ + ε ˆ + ··· + ε ˆ = ε ˆ

α β

α β

α

β

αˆ

ˆ

β

α β α β α β α ˆ ˆ β

= + εˆ

ˆ

ˆ

= αˆ + β + εˆ

=

=

ˆ

( αˆ β )

αˆ

∂αˆ

=

=

ˆ

( αˆ β ) =

 

ˆ

β

ˆ

∂ β

=

=

ˆ

( αˆ β ) =

− α ˆ − β ) =   ˆ β ∂ ˆ ∂ β = −

/∂αˆ

ˆ

=

/∂ β =

αˆ

ˆ

αˆ β

=

β

ˆ

=

¯

=

=

¯

ˆ

¯ αˆ β =

¯

⇐⇒

ˆ

αˆ = β ¯

¯

ˆ

αˆ β

¯

¯

(

¯ β ¯) β

ˆ

¯

ˆ

=

ˆ

β

ˆ α ˆ = − β ¯ ¯ ˆ α ˆ − β ¯ ¯ −

(

¯ β ¯) β

ˆ

¯

ˆ

=

¯

¯ + β β

ˆ

¯

ˆ

=

β ˆ =

¯

¯

¯

¯

¯

= ( ) ¯

=

ˆ

β

[ ( )] = ( , )

ˆ

β

= ( , )/ ( )

( , )

( ) = P ( ¯) = P (

¯ + ¯ ) = P

¯ P + ¯ =

P

¯ ¯ + ¯ = P ¯ ( , ) = P [( ¯)( ¯)] =

P [ ¯ ¯ + ¯ ¯] = P ¯ ¯ ¯ ¯ + ¯ ¯ = P ¯ ¯

¯ + ¯ ¯] = P − ¯ ¯ − ¯ ¯ + ¯ ¯ =

= α + β + ε

ˆ

β

= ( , )

( )

ˆ

¯

αˆ = β

¯

= α + β + ε ˆ β = ( , ) ( ) ˆ ¯

= α + β + ε

ˆ

ˆ = αˆ + β

ˆ

ˆ

β

ˆ

β

ˆ

αˆ

αˆ

= α + β + ε ˆ ˆ = α ˆ + β ˆ ˆ β

( | )

ˆ

= α + β + ε

( | ) = (α + β + ε| ) = α + β + (ε| )

(ε| ) =

( | ) = α + β

ˆ

( | ) = αˆ + β = ˆ

ε | ) = α + β + ( ε | ) ( ε | )

= α + β + ε

( | ) = α + β

ˆ

ˆ

ˆ = αˆ + β

( | ) = αˆ + β

ˆ

ˆ

β

⇐⇒

ˆ

β

 

ˆ

β

αˆ

ˆ

αˆ

⇐⇒

β ⇔ ( | ) = α ˆ + β ˆ ˆ β ⇐⇒ ˆ β

α ˆ

αˆ

α ˆ

ˆ

ˆ = . + .

β

αˆ

ˆ ˆ = . + . β α ˆ

ˆ = . + .

ˆ

β

αˆ

ˆ = − . + . ˆ β α ˆ

= α + β + ε

= α + β + ε

α β

αˆ

ˆ

= αˆ + β + εˆ

ˆ

β α β

ˆ

α β

αˆ

β

ε = α + β + ε α β α ˆ ˆ = α ˆ +

ˆ

α β

αˆ

β

ˆ α β α ˆ β → → →

= α + β + ε

ε

(ε ) = σ (ε , ε ) = (ε , ) =

(ε ) =

= α + β + ε ε ( ε ) = σ ( ε , ε
= α + β + ε ε ( ε ) = σ ( ε , ε

ˆ

αˆ

β

ˆ

αˆ α β

αˆ β

β

ˆ

β α

ˆ α ˆ → β ˆ α ˆ α β α ˆ β β ˆ β

| β β | > δ =

ˆ

δ >

ˆ

β = β

ˆ

β β

→ ∞ | β − β | > δ = ˆ ∀ δ > ˆ β

ˆ

αˆ

β

ˆ

β β

ˆ α ˆ β ˆ β β

= α + β + ε

ε ( , σ )

ˆ

β

= ( , )

( )

σ β = σ

ˆ

( )

ˆ

αˆ = β ¯

¯

σ

αˆ = σ

( )

σ

) ˆ β = ( , ) ( ) σ β = σ ˆ ( )

σ = (ε) = (ε (ε)) = ε

ε

σˆ =

εˆ

=

σˆ =

εˆ

=

εˆ ε

( ε ) = ( ε − ( ε )) = ε ε σ ˆ =

= α + β + ε

ε ( , σ )

β ˆ = ( , )

( )

σˆ β = σˆ

ˆ

( )

ˆ αˆ = ¯ − β ¯ σˆ αˆ = σˆ ( )
ˆ
αˆ =
¯
− β ¯
σˆ αˆ = σˆ
( )

σˆ β = σˆ

ˆ

(

)

σˆ αˆ = σˆ

( )

( )

σˆ

σ ˆ β = σ ˆ ˆ ( ) σ ˆ α ˆ = σ ˆ

( )

( )

( )

σˆ

σ ˆ

σ ˆ
σ ˆ

= α + β + ε

ˆ = . +

(

. )

.

( . )

= . +

(

. )

(

. ) + εˆ

.

= α + β + ε ˆ = − . + ( . ) . (